A Nonexercise Estimate of Cardiorespiratory Fitness Using a Symptom Questionnaire and Clinical Variables. Issue 4 (26th July 2022) - Myers, Jonathan; Chan, Khin; Tan, Isabelle M. C.; Bail, Nicholas; Kamil-Rosenberg, Shirit; Zell, Hunter; Waheed, Tabbasum; Mathew, Pooja
Abstract : Cardiorespiratory fitness (CRF) has recently been classified as a primary risk factor, but determining CRF requires an exercise test. We applied a symptom questionnaire as part of a nonexercise model to estimate CRF (eCRF). We observed that eCRF provided mortality risks that were similar to those from maximal exercise testing. Abstract : Purpose: Cardiorespiratory fitness (CRF) has recently been recognized as a risk factor for mortality, but it is not routinely measured in clinical settings. The purpose of this study was to assess a nonexercise method to estimate CRF (eCRF) and its association with mortality in a clinically referred population. Methods: A symptom tool, termed the Veterans Specific Activity Questionnaire (VSAQ), and nonexercise clinical variables were obtained from 1545 clinically referred subjects (60 ± 13 yr), and followed for a mean of 5.6 ± 4.2 yr. The VSAQ along with nonexercise clinical and historical variables was used to develop a multivariate model to predict achieved CRF from maximal exercise testing. Proportional hazards analysis was used to assess the association between measured and eCRF and all-cause mortality. Results: The eCRF model was significantly associated with achieved CRF (multiple R = 0.67, P < .001). Mean achieved CRF from maximal treadmill testing and eCRF were similar (8.6 ± 5.0 metabolic equivalents [METs] vs 8.7 ± 4.7 METs respectively, P = .27). Achieved CRF and eCRF performed similarly for predicting mortality. After full adjustment, each 1 MET higher increment in achieved CRF and eCRF was associated with 19% and 26% reductions in mortality risk, respectively. Compared with the lowest fit group (<5 METs), the highest CRF groups (>11 METs) had 88% and 87% lower risks for mortality for achieved CRF and eCRF, respectively. Conclusions: A multivariable nonexercise model featuring a symptom questionnaire combined with clinical variables that are readily available during a typical clinical encounter had a reasonably strong association with achieved CRF and exhibited prognostic characteristics that were similar to achieved CRF.